2013
DOI: 10.1111/iju.12281
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms in female patients with pelvic organ prolapse: Efficacy of pelvic floor reconstruction

Abstract: Abbreviations & AcronymsObjective: To evaluate the impact of pelvic floor reconstruction on lower urinary tract symptoms in patients with pelvic organ prolapse. Methods: We carried out a prospective study at a single institution. A total of 223 female patients who underwent tension-free vaginal mesh surgery for pelvic organ prolapse between January 2006 and February 2010 were enrolled and prospectively evaluated. A total of 171 cases with concurrent stress urinary incontinence (76% of all cases) underwent conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…Obinata et al. reported an anatomical cure (defined as POP‐Q stage 0) rate of 91% at 12 months with improved lower urinary tract symptoms . and Miller et al.…”
Section: Discussionmentioning
confidence: 99%
“…Obinata et al. reported an anatomical cure (defined as POP‐Q stage 0) rate of 91% at 12 months with improved lower urinary tract symptoms . and Miller et al.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of adverse events was higher in the TVM group; however, considering the lower cost burden in the TVM group, they were likely to be minor adverse events. Several previous studies on TVM carried out in high‐volume hospitals showed significant improvement in terms of voiding function and sexual function after the surgery . These findings suggest that the performance of TVM surgery by experienced surgeons in high‐volume centers could achieve lower complication rates.…”
Section: Discussionmentioning
confidence: 57%
“…Several previous studies on TVM carried out in high-volume hospitals showed significant improvement in terms of voiding function and sexual function after the surgery. 11,[23][24][25] These findings suggest that the performance of TVM surgery by experienced surgeons in high-volume centers could achieve lower complication rates.…”
Section: Discussionmentioning
confidence: 82%
“…A recent prospective study on 223 female patients undergoing tension-free vaginal mesh surgery for POP, found a post-operative improvement of LUTS in the majority of patients presenting with POP. This study also identified that a lower (e.g., worse) score on an OAB questionnaire was a significant predictive factor for poor post-operative International Prostate Symptoms Score when evaluating the severity of LUTS in both men and women (Hsiao, Lin, & Kuo, 2013;Obinata et al, 2013) (level of evidence = 2).…”
Section: Pelvic Organ Prolapsementioning
confidence: 71%